Analisis Kerusakan Pompa Pendingin Air Laut pada Mesin Induk di Mv. Manalagi Wanda - Fikri Aldiyansyah; Sugeng Marsudi; Rodlitul Awwalin (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This study aims to identify the causes of sea water cooling pump failure, analyze its impact on the main engine cooling system, and explain the corrective actions taken to restore pump performance on board MV. Manalagi Wanda. The sea water cooling pump is one of the essential auxiliary machines responsible for circulating seawater as a cooling medium to maintain the main engine operating temperature within a safe range during ship operations. This research employed a descriptive qualitative method with data collected through direct observation, interviews with the Chief Engineer, Fourth Engineer, and Foreman, as well as documentation during the sea practice period. The collected data were analyzed to determine the relationship between pump component failures and the decline in the performance of the main engine cooling system. The findings revealed that the pump pressure decreased from 2.4 bar to 1.4 bar, causing the main engine High Temperature (HT) to rise from 80.5°C to 82.5°C. Inspection and dismantling of the pump identified damage to the mechanical seal, bearing, and shaft. These damaged components resulted in leakage, excessive vibration, unstable pump rotation, and reduced seawater flow rate. Corrective maintenance was carried out by replacing the damaged components with new parts according to the manufacturer's specifications. After reassembly and a successful test run, the pump pressure returned to 2.4 bar, while the HT temperature decreased to approximately 80.0°C, allowing the cooling system to operate normally and efficiently once again.